Literature Review : Pengaruh Stres Dan Pola Tidur Terhadap Kejadian Preeklampsia Pada Ibu Hamil - Kaila Azkiatunnisak; Rr. Catur Leny Wulandari (Jurnal Kebidanan Besurek, 2026)
This literature review aimed to examine the impact of stress and sleep patterns on the incidence of preeclampsia in pregnant women. Articles published between 2020 and 2025 were retrieved from PubMed, Google Scholar and ScienceDirect using relevant keywords and selected according to predetermined inclusion and exclusion criteria, resulting in ten relevant studies for analysis. The reviewed studies involved pregnant women with and without preeclampsia using a cross-sectional design. The findings indicate that high stress levels and poor sleep quality were significantly associated with an increased risk of preeclampsia through hormonal imblance, autonomic nervous system activation, inflammatory responses, and endothelial dysfunction. Prolonged psychological stress and persistent sleep disturbances were also found to contribute to blood pressure instability during pregnancy. In addition, poor sleep quality may furher intensifty psychological stress and worsen maternal health conditions,